Evaluation of a variable speed limit system using a hierarchical framework under a connected vehicles environment: a case study of a field test in Seattle. Issue 9 (3rd July 2020) - Qi, Xinzhou; Sun, Tuo; Ma, Wanjing; Wang, Ling; Yu, Chunhui
Abstract : Variable speed limit (VSL) system has been recognised as an active traffic management strategy to improve traffic safety and operational efficiency. The development of connected vehicle (CV) technologies have a potential to improve VSL systems because CVs can provide continuous and precise traffic condition as the input of VSL algorithm as well as real‐time recommended speed to drivers. To demonstrate the improvement of the VSL performance from CV technologies, this study presents the evaluation of a VSL system's safety and operational impact on CVs, non‐CVs, and overall traffic conditions, based on a field test in interstate 5 corridor, Seattle. A hierarchical evaluation framework was proposed to explore the effectiveness of the implemented algorithm. The framework consists of three parts, i.e. manoeuvring, safety, and operation. Each part conducts data analysis and statistical tests from traffic sensors and CVs. The findings indicate that the VSL system is able to inform drivers to follow the recommended speed and improve traffic operation even at a low penetration rate. However, the stability of traffic flow is decreased in certain sections. Therefore, the potential improvement of the VSL algorithm is presented based on the findings.